1992
DOI: 10.1128/jb.174.22.7112-7120.1992
|View full text |Cite
|
Sign up to set email alerts
|

Phenol hydroxylase from Trichosporon cutaneum: gene cloning, sequence analysis, and functional expression in Escherichia coli

Abstract: A cDNA clone encoding phenol hydroxylase from the soil yeast Trichosporon cutaneum was isolated and characterized. The clone was identified by hybridization screening of a bacteriophage lambda ZAP-based cDNA library with an oligonucleotide probe which corresponded to the N-terminal amino acid sequence of the purified enzyme. The cDNA encodes a protein consisting of 664 amino acids. Amino acid sequences of a number of peptides obtained by Edman degradation of various cleavage products of the purified enzyme wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 69 publications
2
38
2
Order By: Relevance
“…Putative ADP and FAD binding sequences of DntB aligned with those of other proteins (DntB, MNC monooxygenase from Burkholderia sp. strain DNT; TbuD [18], phenol-cresol hydroxylase from Pseudomonas pickettii PKO1; NahG [48], salicylate hydroxylase from P. putida PpG7; TfdB [29], 2,4-dichlorophenol hydroxylase from Alcaligenes eutrophus JMP134; PhyA [17], phenol hydroxylase from T. cutaneum; PobA [9], p-hydroxybenzoate hydroxylase from Pseudomonas aeruginosa; AlkT [8], rubredoxin reductase from Pseudomonas oleovorans; PheA [27], phenol 2-monooxygenase from Pseudomonas sp. strain EST1001; TodA [50], ferredoxin oxidoreductase of toluene dioxygenase from P. putida F1; BphG [10], ferredoxin oxidoreductase of biphenyl dioxygenase from Pseudomonas strain LB400; PcpB [28], pentachlorophenol-4-monooxygenase from Flavobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Putative ADP and FAD binding sequences of DntB aligned with those of other proteins (DntB, MNC monooxygenase from Burkholderia sp. strain DNT; TbuD [18], phenol-cresol hydroxylase from Pseudomonas pickettii PKO1; NahG [48], salicylate hydroxylase from P. putida PpG7; TfdB [29], 2,4-dichlorophenol hydroxylase from Alcaligenes eutrophus JMP134; PhyA [17], phenol hydroxylase from T. cutaneum; PobA [9], p-hydroxybenzoate hydroxylase from Pseudomonas aeruginosa; AlkT [8], rubredoxin reductase from Pseudomonas oleovorans; PheA [27], phenol 2-monooxygenase from Pseudomonas sp. strain EST1001; TodA [50], ferredoxin oxidoreductase of toluene dioxygenase from P. putida F1; BphG [10], ferredoxin oxidoreductase of biphenyl dioxygenase from Pseudomonas strain LB400; PcpB [28], pentachlorophenol-4-monooxygenase from Flavobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The gene (KRH_22060) adjacent to the probable meta-cleavage gene cluster may encode phenol 2-monooxygenase (EC 1.14.13.7) participating in the oxidation of phenol derivatives into o-diols, which are then channeled into the homoprotocatechuate catabolic pathway. The enzyme from Trichosporon cutaneum, a soil-living yeast, is known to possess a broad substrate specificity hydroxylating simple hydroxyl-, amino-, methyl-, and halogen-substituted phenols (17). The K. rhizophila DC2201 enzyme is similar (35% identity) to the eukaryotic enzyme from T. cutaneum, although the exact substrate specificity of the K. rhizophila enzyme is not known.…”
mentioning
confidence: 99%
“…Quantification of the various bands seen in the Southern blot revealed that, if the DNA shown in Fig. 1B, (21) (35,66) and in genes from Neurospora crassa and Aspergillus species (2,80). Codons ending in A are avoided, and the ones ending in pyrimidines, especially C, are preferred.…”
Section: Resultsmentioning
confidence: 99%